2017
DOI: 10.15587/2519-4984.2017.97208
|View full text |Cite
|
Sign up to set email alerts
|

Features of using the problem teaching methods in psychological and pedagogical training of future teachers of professional and technical educational institutions

Abstract: ОСОБЛИВОСТІ ВИКОРИСТАННЯ МЕТОДІВ ПРОБЛЕМНОГО НАВЧАННЯ У ПСИ-ХОЛОГО-ПЕДАГОГІЧНІЙ ПІДГОТОВЦІ МАЙБУТНІХ ВИКЛАДАЧІВ ПРОФЕСІЙНО-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The study showed some specifics in the realization of the opportunities of problem-based learning (Kryvylova, 2017) for the development of students' research competence depending on the types of training (theoretical, practical). In the process of theoretical learning, the specifics of problem-based learning is that students are mainly involved in search to find answers to problem questions, problem-solving.…”
Section: Discussionmentioning
confidence: 98%
“…The study showed some specifics in the realization of the opportunities of problem-based learning (Kryvylova, 2017) for the development of students' research competence depending on the types of training (theoretical, practical). In the process of theoretical learning, the specifics of problem-based learning is that students are mainly involved in search to find answers to problem questions, problem-solving.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the experience of other countries in enhancing higher education quality is vital. As Kravchenko, et al, [14], and Krivilova, et al, [15] note, the primary goal of education is not just knowledge transfer but also to equip future specialists with the ability to independently analyse and make strategic decisions in a complex and competitive business environment. Economies worldwide require competent professionals who can quickly analyse complex situations and make optimal decisions, considering the risks associated with erroneous choices.…”
Section: Ethical Considerationsmentioning
confidence: 99%